2022
DOI: 10.22159/ijcpr.2022v14i3.1975
|View full text |Cite
|
Sign up to set email alerts
|

Recent Method Development by Analytical Techniques of New Fda Approved Rugs in 2021

Abstract: In this present situation increase in the number of diseases has been observed and several new medications are invented and have been developed to treat various disorders, which are approved by FDA. But before these drugs come to market it must undergo several procedures. The validation and analytical process of a new drug development helps in ensuring its purity and reliability. This process involves the use of various analytical techniques to collect data about the drug. This review includes various types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The animal dose of IBH was estimated with relevance to the human dose by using the formula below. The dosage form was administered through the gastric intubation method [18].…”
Section: Subject Selectionmentioning
confidence: 99%
“…The animal dose of IBH was estimated with relevance to the human dose by using the formula below. The dosage form was administered through the gastric intubation method [18].…”
Section: Subject Selectionmentioning
confidence: 99%
“…By understanding the underlying mechanisms of these conditions and developing drugs that target specific pathways, researchers and clinicians can provide more effective and personalized treatment options for patients with rare and complex diseases. There are currently no available methods for the bioanalysis of maralixibat in any type of biological matrix [13]. To address this gap, a recent study has reported the development of a novel bioanalytical method for the quantification of maralixibat in biological samples.…”
Section: Introductionmentioning
confidence: 99%